Effects of surgical implantation of electronic tags in fishes: a review and meta-analysis - Mitchell B. Shorgan; Graham D. Raby; Amber L. Fedus; Bradley E. Howell; Laura S. E. Haniford; Leah C. Howitt; Natalie V. Klinard; Jordan K. Matley; Jacob W. Brownscombe; Steven J. Cooke; Aaron T. Fisk (Reviews in Fish Biology and Fisheries, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Application of a population status model on several recreational lake trout (Salvelinus namaycush) fisheries in Manitoba, Canada - Giulio Navarroli; Bradley E. Howell; Andrew W. R. Klein; Eric J. Mullen; Olivier Morissette; Michael D. Rennie; Caleb T. Hasler (Environmental Biology of Fishes, 2025)

Characterization of adult hippocampal neurogenesis in adult and aged genetically diverse mice - Adele E. Finch; Avery D. McNamara; Kristen D. Onos; Kelly J. Keezer; Gareth R. Howell; Ashley E. Webb (GeroScience, 2025)
Adult hippocampal neurogenesis—the generation of new neurons in the adult brain—declines with age, contributing to cognitive deficits in aging. While the majority of mammalian studies on neurogenesis have utilized inbred mouse strains, these models do not fully capture the genetic diversity of humans, limiting the translational relevance of their findings. The Diversity Outbred (DO) mouse model, a genetically heterogeneous population, provides a promising alternative to traditional inbred strains. In this study, we investigated how genetic diversity influences hippocampal neurogenesis by comparing neurogenesis in adult and aged Diversity Outbred (DO) mice with the commonly used C57BL/6J inbred strain. While both strains exhibited a decline in neurogenesis with age, DO mice showed significantly lower levels of neurogenesis compared to C57BL/6J mice, even in young adults. Additionally, we observed that the wild-derived CAST/EiJ strain, one of the eight founder strains in the DO model, contributed to this reduction in neurogenesis. Our findings highlight the importance of genetic diversity in neurogenesis research and suggest that the DO model may better represent human genetic diversity associated with age-related decline in neurogenesis.

Estimated golden eagle mortality from wind turbines in the western United States - Jay V. Gedir; Matthew J. Gould; Brian A. Millsap; Paige E. Howell; Guthrie S. Zimmerman; Emily R. Bjerre; Hillary M. White (Biological Conservation, 2025)

Synthesizing the spatial functionality of contemporary stock assessment software to identify future needs for next generation assessment platforms - Aaron M. Berger; Caren Barceló; Daniel R. Goethel; Simon D. Hoyle; Patrick D. Lynch; Jeremy McKenzie; Alistair Dunn; André E. Punt; Richard D. Methot; John Hampton; Clay E. Porch; Richard McGarvey; et al. (Fisheries Research, 2024)

Trajectories and tipping points of piñon–juniper woodlands after fire and thinning - Michala L. Phillips; Cara Lauria; Tova Spector; John B. Bradford; Catherine Gehring; Brooke B. Osborne; Armin Howell; Edmund E. Grote; Renee J. Rondeau; Gillian M. Trimber; Benjamin Robinson; Sasha C. Reed (Global Change Biology, 2024)
Piñon–juniper (PJ) woodlands are a dominant community type across the Intermountain West, comprising over a million acres and experiencing critical effects from increasing wildfire. Large PJ mortality and regeneration failure after catastrophic wildfire have elevated concerns about the long‐term viability of PJ woodlands. Thinning is increasingly used to safeguard forests from fire and in an attempt to increase climate resilience. We have only a limited understanding of how fire and thinning will affect the structure and function of PJ ecosystems. Here, we examined vegetation structure, microclimate conditions, and PJ regeneration dynamics following ~20 years post‐fire and thinning treatments. We found that burned areas had undergone a state shift that did not show signs of returning to their previous state. This shift was characterized by (1) distinct plant community composition dominated by grasses; (2) a lack of PJ recruitment; (3) a decrease in the sizes of interspaces in between plants; (4) lower abundance of late successional biological soil crusts; (5) lower mean and minimum daily soil moisture values; (6) lower minimum daily vapor pressure deficit; and (7) higher photosynthetically active radiation. Thinning created distinct plant communities and served as an intermediate between intact and burned communities. More intensive thinning decreased PJ recruitment and late successional biocrust cover. Our results indicate that fire has the potential to create drier and more stressful microsite conditions, and that, in the absence of active management following fire, there may be shifts to persistent ecological states dominated by grasses. Additionally, more intensive thinning had a larger impact on community structure and recruitment than less intensive thinning, suggesting that careful consideration of goals could help avoid unintended consequences. While our results indicate the vulnerability of PJ ecosystems to fire, they also highlight management actions that could be adapted to create conditions that promote PJ re‐establishment.

A risk assessment for the remote ocean: the case of the South East Atlantic - Holly J. Niner; Siân E. Rees; Giulia La Bianca; Kirsty A. McQuaid; Kerry L. Howell (Frontiers in Marine Science, 2024)
Degradation of the natural world and associated ecosystem services is attributed to a historical failure to include its ‘value’ in decision-making. Uncertainty in the quantification of the relationship between natural capital ‘assets’ that give rise to critical societal benefits and people is one reason for the omission of these values from natural resource management. As this uncertainty increases in marine systems and further still with distance from the coast, the connection between society and natural capital assets is less likely to be included adequately in decision-making. Natural capital assets of Areas Beyond National Jurisdiction (ABNJ), including those of the deep sea, are distant but are known to generate many benefits for society, from the diffuse and broad-scale benefits of climate regulation to the provision of wild fish for food. While our understanding of the precise relationships (the status of asset stocks, ecosystem functions and processes) that control the availability of ecosystem services and the flows of benefits is limited, this does not preclude opening a discourse on how these natural capital assets could best be managed to continue to benefit society. Here we apply a natural capital approach to the South East Atlantic ABNJ, one of the least scientifically understood regions of the planet, and develop a framework for risk assessment. We do this by describing the benefit flows from the natural capital assets of the region, appraising how activities are creating pressures on these flows and whether the controls for these pressures protect them. Our risk register highlights how governance currently favours the protection of direct (extractive) benefit flows from natural capital assets of the region, which are primarily targeted for financial benefit. Without a systems-based framework that can account for the cumulative pressures on natural capital assets their status, associated ecosystem services and benefits are at risk. Such an approach is essential to capture and protect the foundational and often diffuse connections between marine natural capital and global society.

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

Physiological diversity among sympatric, conspecific endosymbionts of coral (Cladocopium C1acro) from the Great Barrier Reef - V. H. Beltrán; E. Puill-Stephan; E. Howells; A. Flores-Moya; M. Doblin; E. Núñez-Lara; V. Escamilla; T. López; M. J. H. van Oppen (Coral Reefs, 2021)

Refining Fisheries Advice With Stock-Specific Ecosystem Information - Jacob W. Bentley; Mathieu G. Lundy; Daniel Howell; Steven E. Beggs; Alida Bundy; Francisco de Castro; Clive J. Fox; Johanna J. Heymans; Christopher P. Lynam; Debbi Pedreschi; Pia Schuchert; Natalia Serpetti; et al. (Frontiers in Marine Science, 2021)
Although frequently suggested as a goal for ecosystem-based fisheries management, incorporating ecosystem information into fisheries stock assessments has proven challenging. The uncertainty of input data, coupled with the structural uncertainty of complex multi-species models, currently makes the use of absolute values from such models contentious for short-term single-species fisheries management advice. Here, we propose a different approach where the standard assessment methodologies can be enhanced using ecosystem model derived information. Using a case study of the Irish Sea, we illustrate how stock-specific ecosystem indicators can be used to set an ecosystem-based fishing mortality reference point (F ECO ) within the “Pretty Good Yield” ranges for fishing mortality which form the present precautionary approach adopted in Europe by the International Council for the Exploration of the Sea (ICES). We propose that this new target, F ECO , can be used to scale fishing mortality down when the ecosystem conditions for the stock are poor and up when conditions are good. This approach provides a streamlined quantitative way of incorporating ecosystem information into catch advice and provides an opportunity to operationalize ecosystem models and empirical indicators, while retaining the integrity of current assessment models and the F MSY -based advice process.

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Annual outbreaks of coral disease coincide with extreme seasonal warming - E. J. Howells; G. O. Vaughan; T. M. Work; J. A. Burt; D. Abrego (Coral Reefs, 2020)

Correction to: Effects of New Zealand blackcurrant extract on sport climbing performance - J. A. Potter; C. I. Hodgson; M. Broadhurst; L. Howell; J. Gilbert; M. E. T. Willems; I. C. Perkins (European Journal of Applied Physiology, 2020)

Effects of New Zealand blackcurrant extract on sport climbing performance - J. A. Potter; C. I. Hodgson; M. Broadhurst; L. Howell; J. Gilbert; M. E. T. Willems; I. C. Perkins (European Journal of Applied Physiology, 2020)

Combining Distribution and Dispersal Models to Identify a Particularly Vulnerable Marine Ecosystem - Rebecca E. Ross; Edward J. G. Wort; Kerry L. Howell (Frontiers in Marine Science, 2019)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Variation in particulate C : N : P stoichiometry across the Lake Erie watershed from tributaries to its outflow - Clay Prater; Paul C. Frost; E. Todd Howell; Susan B. Watson; Arthur Zastepa; Sarah S. E. King; Richard J. Vogt; Marguerite A. Xenopoulos (Limnology and Oceanography, 2017)
Human activities can cause large alterations in biogeochemical cycles of key nutrients such as carbon (C), nitrogen (N), and phosphorus (P). However, relatively little is known about how these changes alter the proportional fluxes of these elements across ecosystem boundaries from rivers to lakes. Here, we examined environmental factors influencing spatial and temporal variation in particulate C : N : P ratios across the Lake Erie watershed from its tributaries to its outflow. Throughout the study, particulate nutrient ratios ranged widely (C : N 2.0–25.8, C : P 32–530, N : P 3.7–122.9), but mean values were generally lower than previous estimates from different aquatic environments. Particulate C : N ratios varied the least across all environments, but C : P and N : P ratios increased between tributaries and coastal areas and throughout the growing season in coastal environments. These ratios also differed temporally in offshore waters as particulate C : P and N : P were higher in the spring and summer and lower in the fall and winter. Particulate C : P ratios also increased between the western/central and eastern basins indicating differential nutrient processing across the lake. These stoichiometric changes were associated with unique environmental factors among ecosystems as tributary stoichiometry was related to terrestrial land use and land cover, coastal ratios were a product of mixing between riverine and offshore waters, and offshore patterns were influenced by differences in temperature and particulate nutrient loading among basins. Overall, by studying changes in particulate C : N : P ratios across the Lake Erie watershed, our study demonstrates the power of using mass balance principles to study nutrient transformations along the aquatic continuum.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Population genetics of reef coral endosymbionts ( Symbiodinium , Dinophyceae) - D. J. Thornhill; E. J. Howells; D. C. Wham; T. D. Steury; S. R. Santos (Molecular Ecology, 2017)
Symbiodinium is a diverse genus of unicellular dinoflagellate symbionts associating with various marine protists and invertebrates. Although the broadscale diversity and phylogenetics of the Symbiodinium complex is well established, there have been surprisingly few data on fine‐scale population structure and biogeography of these dinoflagellates. Yet population‐level processes contribute strongly to the biology of Symbiodinium , including how anthropogenic‐driven global climate change impacts these symbionts and their host associations. Here, we present a synthesis of population‐level characteristics for Symbiodinium , with an emphasis on how phylogenetic affinities, dynamics within and among host individuals, and a propensity towards clonality shape patterns on and across reefs. Major inferences include the following: (i) Symbiodinium populations within individual hosts are comprised mainly of cells belonging to a single or few genetic clones. (ii) Symbiont populations exhibit a mixed mode of reproduction, wherein at least one sexual recombination event occurs in the genealogy between most genotypes, but clonal propagation predominates overall. (iii) Mutualistic Symbiodinium do not perpetually persist outside their hosts, instead undergoing turnover and replacement via the continuous shedding of viable clonal cells from host individuals. (iv) Symbiont populations living in the same host, but on different reefs, are often genetically subdivided, suggesting low connectivity, adaptation to local conditions, or prolific asexual reproduction and low effective population sizes leading to disproportionate success within and among hosts. Overall, this synthesis forms a basis for future investigations of coral symbiosis ecology and evolution as well as delimitation of species boundaries in Symbiodinium and other eukaryotic microorganisms.

Risk algorithms that include pathology adjustment for HER2 amplification need to make further downward adjustments in likelihood scores - D. G. Evans; E. R. Woodward; S. J. Howell; S. Verhoef; A. Howell; F. Lalloo (Familial Cancer, 2017)

Microsatellite allele sizes alone are insufficient to delineate species boundaries in Symbiodinium - E. J. Howells; B. L. Willis; L. K. Bay; M. J. H. van Oppen (Molecular Ecology, 2016)
Symbiodinium are a diverse group of unicellular dinoflagellates that are important nutritional symbionts of reef‐building corals. Symbiodinium putative species (‘types’) are commonly identified with genetic markers, mostly nuclear and chloroplast encoded ribosomal DNA regions. Population genetic analyses using microsatellite loci have provided insights into Symbiodinium biogeography, connectivity and phenotypic plasticity, but are complicated by: (i) a lack of consensus criteria used to delineate inter‐ vs. intragenomic variation within species; and (ii) the high density of Symbiodinium in host tissues, which results in single samples comprising thousands of individuals. To address this problem, Wham & LaJeunesse (2016) present a method for identifying cryptic Symbiodinium species from microsatellite data based on correlations between allele size distributions and nongeographic genetic structure. Multilocus genotypes that potentially do not recombine in sympatry are interpreted as secondary ‘species’ to be discarded from downstream population genetic analyses. However, Symbiodinium species delineations should ideally incorporate multiple physiological, ecological and molecular criteria. This is because recombination tests may be a poor indicator of species boundaries in Symbiodinium due to their predominantly asexual mode of reproduction. Furthermore, discontinuous microsatellite allele sizes in sympatry may be explained by secondary contact between previously isolated populations and by mutations that occur in a nonstepwise manner. Limitations of using microsatellites alone to delineate species are highlighted in earlier studies that demonstrate occasional bimodal distributions of allele sizes within Symbiodinium species and considerable allele size sharing among Symbiodinium species. We outline these issues and discuss the validity of reinterpretations of our previously published microsatellite data from Symbiodinium populations on the Great Barrier Reef (Howells et al . 2013).

A trans‐Atlantic examination of haddock Melanogrammus aeglefinus food habits - J. C. Tam; J. S. Link; S. I. Large; B. Bogstad; A. Bundy; A. M. Cook; G. E. Dingsør; A. V. Dolgov; D. Howell; A. Kempf; J. K. Pinnegar; A. Rindorf; et al. (Journal of Fish Biology, 2016)
The food habits of Melanogrammus aeglefinus were explored and contrasted across multiple north‐eastern and north‐western Atlantic Ocean ecosystems, using databases that span multiple decades. The results show that among all ecosystems, echinoderms are a consistent part of M. aeglefinus diet, but patterns emerge regarding where and when M. aeglefinus primarily eat fishes v . echinoderms. Melanogrammus aeglefinus does not regularly exhibit the increase in piscivory with ontogeny that other gadoids often show, and in several ecosystems there is a lower occurrence of piscivory. There is an apparent inverse relationship between the consumption of fishes and echinoderms in M. aeglefinus over time, where certain years show high levels of one prey item and low levels of the other. This apparent binary choice can be viewed as part of a gradient of prey options, contingent upon a suite of factors external to M. aeglefinus dynamics. The energetic consequences of this prey choice are discussed, noting that in some instances it may not be a choice at all.

Functional connectivity in frontal-striatal brain networks and cocaine self-administration in female rhesus monkeys - K. S. Murnane; K. S. Gopinath; E. Maltbie; J. B. Daunais; Q. K. Telesford; L. L. Howell (Psychopharmacology, 2015)

Novel Mutations Mapping to the Fourth Sodium Channel Domain of Nav1.7 Result in Variable Clinical Manifestations of Primary Erythromelalgia - Roman Cregg; Bisola Laguda; Robert Werdehausen; James J. Cox; John E. Linley; Juan D. Ramirez; Istvan Bodi; Michael Markiewicz; Kevin J. Howell; Ya-Chun Chen; Karen Agnew; Henry Houlden; et al. (NeuroMolecular Medicine, 2013)

The Development of the Washington State Emergency Department Opioid Prescribing Guidelines - Darin E. Neven; Jennifer C. Sabel; Donelle N. Howell; Russell J. Carlisle (Journal of Medical Toxicology, 2012)

In vitro to in vivo extrapolation and species response comparisons for drug-induced liver injury (DILI) using DILIsym™: a mechanistic, mathematical model of DILI - Brett A. Howell; Yuching Yang; Rukmini Kumar; Jeffrey L. Woodhead; Alison H. Harrill; Harvey J. Clewell; Melvin E. Andersen; Scott Q. Siler; Paul B. Watkins (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

Solvent Removal and Spore Inactivation Directly in Dispensing Vials with Supercritical Carbon Dioxide and Sterilant - Jahna Howell; Fengui Niu; Shannon E. McCabe; Wei Zhou; Charles J. Decedue (AAPS PharmSciTech, 2012)

High genetic differentiation and cross-shelf patterns of genetic diversity among Great Barrier Reef populations of Symbiodinium - E. J. Howells; M. J. H. van Oppen; B. L. Willis (Coral Reefs, 2009)

Does sequence polymorphism of FLC paralogues underlie flowering time QTL in Brassica oleracea? - H. Razi; E. C. Howell; H. J. Newbury; M. J. Kearsey (Theoretical and Applied Genetics, 2008)

An integrated AFLP and RFLP Brassica oleracea linkage map from two morphologically distinct doubled-haploid mapping populations - R. L. Sebastian; E. C. Howell; G. J. King; D. F. Marshall; M. J. Kearsey (Theoretical and Applied Genetics, 2000)